Factors Influencing HIV Status Disclosure Among People Living with HIV/AIDS in Mukono District, Uganda: Beyond Health System Support - Gamba, Perry (Journal of Clinical Research In HIV AIDS And Prevention, 2025)
Background HIV status disclosure is a complex process influenced by multiple factors beyond health system support. Understanding these factors is essential for developing comprehensive interventions to promote disclosure and improve HIV prevention and care outcomes. Methods A descriptive cross-sectional study was conducted in 10 health facilities offering comprehensive HIV/AIDS care in Mukono district, Uganda. Data was collected from 317 clients through interview-guided questionnaires. Data was entered using EPI data and analyzed using SPSS version 16, including logistic regression to identify factors associated with disclosure. Results Multiple factors influenced HIV status disclosure. Individual factors included knowledge about HIV (OR=2.34, 95% CI: 1.45-3.78), self-efficacy (OR=3.12, 95% CI: 1.87-5.21), and psychological readiness (OR=2.89, 95% CI: 1.76-4.75). Relationship factors included relationship quality (OR=3.56, 95% CI: 2.13-5.94), communication patterns (OR=2.78, 95% CI: 1.65-4.69), and anticipated partner reaction (OR=4.23, 95% CI: 2.54-7.05). Community factors included perceived stigma (OR=0.34, 95% CI: 0.21-0.56), cultural norms (OR=0.45, 95% CI: 0.27-0.75), and religious beliefs (OR=1.87, 95% CI: 1.12-3.14). Structural factors included economic dependence (OR=0.38, 95% CI: 0.23-0.63) and access to support services (OR=2.45, 95% CI: 1.47-4.08). Conclusions HIV status disclosure is influenced by a complex interplay of individual, relationship, community, and structural factors. Effective interventions to promote disclosure must address these multiple levels of influence, going beyond health system support to create enabling environments for disclosure at the individual, relationship, community, and structural levels.
Keywords: HIV status disclosure; influencing factors; individual factors; relationship factors; community factors; structural factors; Uganda